Double trouble: two retrotransposons triggered a cascade of invasions in Drosophila species within the last 50 years - Almorò Scarpa; Riccardo Pianezza; Hannah R. Gellert; Anna Haider; Bernard Y. Kim; Eric C. Lai; Robert Kofler; Sarah Signor (Nature Communications)
Abstract Horizontal transfer of genetic material in eukaryotes has rarely been documented over short evolutionary timescales. Here, we show that two retrotransposons, Shellder and Spoink, invaded the genomes of multiple species of the melanogaster subgroup within the last 50 years. Through horizontal transfer, Spoink spread in D. melanogaster during the 1980s, while both Shellder and Spoink invaded D. simulans in the 1990s. Possibly following hybridization, D. simulans infected the island endemic species D. mauritiana (Mauritius) and D. sechellia (Seychelles) with both TEs after 1995. In the same approximate time-frame, Shellder also invaded D. teissieri, a species confined to sub-Saharan Africa. We find that the donors of Shellder and Spoink are likely American Drosophila species from the willistoni, cardini, and repleta groups. Thus, the described cascade of TE invasions could only become feasible after D. melanogaster and D. simulans extended their distributions into the Americas 200 years ago, likely aided by human activity. Our work reveals that cascades of TE invasions, likely initiated by human-mediated range expansions, could have an impact on the genomic and phenotypic evolution of geographically dispersed species. Within a few decades, TEs could invade many species, including island endemics, with distributions very distant from the donor of the TE.